Condensed-Phase Effects on the Structural Properties of FCH[subscript]2CN-BF[subscript]3 and CICH[subscript]2CN-BF[subscript]3 - Buchberger, Amanda Rae; Bloomgren, Kaitlin M.; Danforth, Samuel J. (My University, 2013)
The purpose of this study was to assess the degree to which bulk, condensed-phase environments affect the structural properties of FCH[subscript]2CN-BF[subscript]3 and CICH[subscript]2CN-BF[subscript]3, using both low-temperature IR and computations.
Color poster with text, diagrams, graphs, images, and charts.
Keywords: Molecular structure; Reactivity (Chemistry); Solvents; Chemistry--Computations; Infrared spectroscopy; Posters